NON-GENETIC FACTORS AFFECTING THE MORTALITY IN KURDI LAMBS - O. Raoof, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was carried out using 94 ewes at Erbil plain - Kurdistan region-Iraq, during the period from May 2016 to April 2017. The overall mean mortality rates from birth to 7 days and from 8 days to weaning age were 8.6 and 6.6%, respectively. Age of dam, type of birth, weight of the dam at matting, Body Condition Score (BCS) and birth weight had an important significant (P